Efectos de la crisis económica internacional y del fenómeno del niño sobre la balanza de pagos del Perú, 1997- 1999 - Rozenberg, Arnoldo (2000)
This paper evaluates the effects of the externa1 crisis (from 1997 to 1999) on the main accounts of the Peruvian’s balance of payments. Estimating mainly its effects on the trade, services, and income accounts of the current balance and financia1 accounts. Also, this paper tries to estimate approximately the probable effects of ‘el Niño’ (1997-1998) on the external sector, to find out more approximate values from the direct effects of these serious external shocks on the commercial and financia1 flows; separating them into autonomous and balancing transactions of the balance of payments. Also, it analyzes the limited use of macroeconomics policy by the Peruvian government to counteract the crisis; or rather the implementation of few partial and late measures to overcome the effects of the domestic contraction and recession,generated by both shocks of externa1 origin.